2022
DOI: 10.1021/acsphotonics.2c00029
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for Addressing the Low Quantum Efficiency of Nanowire Photodetectors

Abstract: Nanowire photodetectors are attractive for their high speed and responsivity, enabled by small junction capacitance and high internal gain. However, their effectiveness is hampered by a low quantum efficiency due to poor light coupling to their intrinsically small size. The optically sensitive area can be increased by connecting arrays of standing nanowires (pillars) in parallel under a single readout, but the increase in dark current and total capacitance might reduce pixel sensitivity. The net effect has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Unlike APDs, there is no need for HPTs to apply high bias voltage for APD operation to achieve high photocurrent gain, and so there is no excess avalanche noise characteristic [208]. In this respect, InP/InGaAs-based SWIR HPTs and FPA imagers with ultrahigh sensitivity have been demonstrated very recently [209,210], making HPT a promising candidate to extend to the MWIR and LWIR. Meanwhile, MWIR and LWIR HPTs based on Sb-T2SLs have been demonstrated by CQD at Northwestern University.…”
Section: High Sensitivity Pds With Internal Gainmentioning
confidence: 99%
“…Unlike APDs, there is no need for HPTs to apply high bias voltage for APD operation to achieve high photocurrent gain, and so there is no excess avalanche noise characteristic [208]. In this respect, InP/InGaAs-based SWIR HPTs and FPA imagers with ultrahigh sensitivity have been demonstrated very recently [209,210], making HPT a promising candidate to extend to the MWIR and LWIR. Meanwhile, MWIR and LWIR HPTs based on Sb-T2SLs have been demonstrated by CQD at Northwestern University.…”
Section: High Sensitivity Pds With Internal Gainmentioning
confidence: 99%
“…Similarly, we used this ROIC‐based high throughput measurement approach to study different methods for increasing the quantum efficiency of nano‐photodetectors. [ 27 ] A large number of different device types were fabricated side‐by‐side on a ROIC. Another theoretical model we developed suggested that an array of connected small phototransistors could be more sensitive than a single large device with the same overall area.…”
Section: Photodetector Characterization Based On Roicmentioning
confidence: 99%
“…This effect can hinder imaging and detection performance metrics, such as quantum efficiency. Some solutions to improve the optical absorption rely on stacking thick layers of low‐dimensional materials while maintaining their dimensionality (e.g., solution‐dispersed flakes, [ 26 ] or dense vertical arraying of nanowires [ 27 ] ). In addition, photonics solutions discussed in the later sections could be used for a wide range of materials.…”
Section: Imaging With Low‐dimensional Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the number of structures increases, the pixel's total dark current also increases; and our second FPA shows that triple detectors showed a slightly lower operability than double detectors (73.5% vs. 78.0%). Therefore, the appropriate number of structures and their spacing requires optimization to obtain both high operability and sensitivity [26]. In addition, the mechanical pressure and temperature condition of the flip-chip bonding process can also be optimized for submicron pixels, in order to achieve high pixel operability with a minimum number of detector structures.…”
Section: Strategies For Improving the Operability Of Scaled Photodete...mentioning
confidence: 99%